Answer:
Standard form of the given expression is [tex]x + 1 = x ( x - 1 ) \implies x^2 -2x - 1 = 0[/tex]
Step-by-step explanation:
Here, the given expression is:
x + 1 = x ( x - 1 )
DISTRIBUTIVE PROPERTY: A(B - C) = AB - AC
Now, simplifying the given expression, we get
[tex]x + 1 = x ( x - 1 ) \\\implies x + 1 = x ( x) - x(1 ) \\\implies x + 1 = x^2 -x\\\implies x^2 -x -x - 1 = 0\\\implies x^2 -2x - 1 = 0[/tex]
The standard form of a quadratic equation is : [tex]ax^2 + bx + c[/tex]
Hence, comparing the simplified expression with the Quadratic formula ,we get, [tex]x + 1 = x ( x - 1 ) \implies x^2 -2x - 1 = 0[/tex]